Environmental Restrictors to Occupational Participation in Old Age: Exploring Differences across Gender in Puerto Rico - Orellano-Colón, Elsa M. (Int J Environ Res Public Health, 2015)
Many older adults face challenges that prevent them from accomplishing common daily activities such as moving around, home maintenance, and leisure activities. There is still a need to examine and understand how environmental factors impact daily participation across gender. This study sought to make a qualitative comparison of gender differences regarding environmental barriers to participation in daily occupations from the perspectives of older adults who live alone in Puerto Rico. Twenty-six Hispanic older adults, 70 years or older participated in this study. We used a descriptive qualitative research design in which researchers administered an in-depth interview to each participant. The results elucidated that women were more likely than men to experience restricted participation due to lack of accessibility of the built environment and transportation systems. The findings could help with the development of tailored, occupation-based, preventive interventions that address gender specific environmental barriers and promote greater participation among both women and men. Further research is required to explore whether these environmental barriers to occupational participation remain consistent across living situations, socioeconomic status and ethnicity.